2005
DOI: 10.1007/s11145-004-2345-x
|View full text |Cite
|
Sign up to set email alerts
|

How do the spellings of children with dyslexia compare with those of nondyslexic children?

Abstract: Children with dyslexia are believed to have very poor phonological skills for which they compensate, to some extent, through relatively well-developed knowledge of letter patterns. We tested this view in Study 1 by comparing 25 dyslexic children and 25 younger normal children, chosen so that both groups performed, on average, at a second-grade spelling level. Phonological skill was assessed using phoneme counting and nonword spelling tasks. Knowledge of legal and illegal letter patterns was tested using a spel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
69
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 19 publications
9
69
0
4
Order By: Relevance
“…The older children with dyslexia appeared somewhat less likely to maintain the entire spelling of the stem when writing an inflected word, as in the studies of Carlisle (1987) and Hauerwas and Walker (2003), but the difference was not statistically reliable in the present experiment. The many similarities that we found between the spellings of older children with dyslexia and younger typical children support the results of several previous studies in which a spelling-level match design was used (Bourassa & Treiman, 2003;Cassar, Treiman, Moats, Pollo, & Kessler, 2005;Nelson, 1980). In those studies, older children with dyslexia performed very similarly to younger typical children in use of phonological information in spelling and in knowledge of legal and illegal spelling patterns.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The older children with dyslexia appeared somewhat less likely to maintain the entire spelling of the stem when writing an inflected word, as in the studies of Carlisle (1987) and Hauerwas and Walker (2003), but the difference was not statistically reliable in the present experiment. The many similarities that we found between the spellings of older children with dyslexia and younger typical children support the results of several previous studies in which a spelling-level match design was used (Bourassa & Treiman, 2003;Cassar, Treiman, Moats, Pollo, & Kessler, 2005;Nelson, 1980). In those studies, older children with dyslexia performed very similarly to younger typical children in use of phonological information in spelling and in knowledge of legal and illegal spelling patterns.…”
Section: Discussionsupporting
confidence: 88%
“…Confirming the preliminary findings of Bourassa and Treiman (2003), we also found that older children with dyslexia often misspell flaps. This outcome supports the idea that the same aspects of phonology that cause difficulties for typical beginning spellers also cause difficulties for older children with dyslexia (e.g., Bourassa & Treiman, 2003;Cassar et al, 2005;Moats, 1983).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, most research on spelling difficulties concerns children with dyslexia who are in the early stages of spelling instruction (Cassar et al, 2005;Bourassa et al, 2006) and the few data that are available seem to be contradictory.…”
Section: Spelling Performance In Students With Dyslexiamentioning
confidence: 99%
“…Several other studies also failed to find a disproportionally large number of phonological errors in writers with dyslexia (Bourassa & Treiman, 2003;Nelson, 1980). Cassar et al (2005), for instance, compared the spellings of English speaking children with dyslexia (mean age 11.7 years) with those of non-dyslexic children in primary education (mean age 6.8 years), using a spelling-level matched design. The authors argued that children with dyslexia had difficulties with the same linguistic structures as typically developing (but younger) spellers.…”
Section: Spelling Performance In Students With Dyslexiamentioning
confidence: 99%
See 1 more Smart Citation